Recent achievements in perovskite solar cells - B.R. Ilyassov; N.Kh. Ibrayev (Қарағанды университетінің хабаршысы. Физика сериясы)
Hybrid (organo-inorganic) perovskite materials are potential candidate as a photoactive materals for photovoltaics. Currently, many research groups have been focused on designing the perovskite materials in such a way so that it can harness the broad spectrum of visible light wavelength. Hybrid perovskites such methylammonium lead halides reveal unique photovoltaic and charge transport properties. The main objectives of this article are to provide some recent research progress on perovskite nanomaterials for solar cell application. Therefore, this mini review paper summarizes some recent development of organic-inorganic perovskite materials of different research groups and provides some useful insights for its future improvement.